An American Tune : A Novel - Shoup, Barbara (Book collections on Project MUSE., 2012)
While reluctantly accompanying her husband and daughter to freshman orientation at Indiana University, Nora Quillen hears someone call her name, a name she has not heard in more than 25 years. Not even her husband knows that back in the '60s she was Jane Barth, a student deeply involved in the antiwar movement. An American Tune moves back and forth in time, telling the story of Jane, a girl from a working-class family who fled town after she was complicit in a deadly bombing, and Nora, the woman she became, a wife and mother living a quiet life in northern Michigan. An achingly poignant account of a family crushed under the weight of suppressed truths, An American Tune illuminates the irrevocability of our choices and how those choices come to compose the tune of our lives.